2018
DOI: 10.1039/c7ra13751f
|View full text |Cite
|
Sign up to set email alerts
|

Numbers of cyanovinyl substitutes and their effect on phenothiazine based organic dyes for dye-sensitized solar cells

Abstract: A series of phenothiazine based dyes (OMS1-3), comprising different conjugation lengths and numbers of electron deficient (cyanovinyl) moieties with cyanoacrylic acid as an anchor, have been synthesized. The dyes display broad UV-visible absorption, from 389 nm to 484 nm. The higher molar extinction coefficient and longer absorption peak are achieved as the conjugation length and numbers of electron deficient units increase. The cell performance based on these dyes exhibits efficiencies ranging from 0.68-4.00%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A sequence of PTZ‐based dyes ( 232‐234 ) has been synthesized, containing various lengths of conjugation and numbers of cyanovinyl (electron‐deficient) groups with CA as acceptor by Chen et al 140 The dyes exhibited a wide UV absorption from 389 nm to 484 nm. As the length of the conjugation and the number of electron‐deficient units increase, the increased MEC and extended absorption peak were attained.…”
Section: Recent Developments In Ptz‐based Dyesmentioning
confidence: 99%
“…A sequence of PTZ‐based dyes ( 232‐234 ) has been synthesized, containing various lengths of conjugation and numbers of cyanovinyl (electron‐deficient) groups with CA as acceptor by Chen et al 140 The dyes exhibited a wide UV absorption from 389 nm to 484 nm. As the length of the conjugation and the number of electron‐deficient units increase, the increased MEC and extended absorption peak were attained.…”
Section: Recent Developments In Ptz‐based Dyesmentioning
confidence: 99%
“…Yung et al recently reported a series of PTZ-based photosensitisers for dye-sensitized solar cells with cyanoacetic acid as an anchoring group along with astute alteration of conjugation length in their molecular design, which resulted in improved power conversion efficiency and broadband incident photon conversion efficiency. 12 Likewise, in the case of PTZ-based organic solar cells, an efficiency of about 2% was realized with a fullerene derivative as acceptor. 13 The extensive conjugation mediated between PTZ and fullerene propelled strong intramolecular charge transfer, which thereby promoted the photovoltaic conversion efficiency in the visible light range from 400 to 800 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that electropolymerization can be used as an alternative tool for fabricating conjugated polymer-modified electrodes without the need for any catalyst and template. , Regarding the exceptional processability of conducting polymers obtained from electropolymerization, substantial progress has been made toward the development of electrodes from various aromatic monomers via electropolymerization. , Among these monomers, phenothiazine and its derivatives, comprising electron-rich N and S, are recognized as highly popular building units for fabricating electrodes due to the reversible radical cation formation and tunable redox property. The inherent features enable development of polyphenothiazine-modified electrodes via electropolymerization for applications in solar cells. If we introduce phenothiazine polymers into photoelectrodes for developing PEC sensors via electropolymerization, such sensors could efficiently address the challenge of film formation for sensitive and accurate determination of various target biomolecules. However, as far as we are concerned, these fabricated electrodes still lack functional groups, being adverse to modification with functional substances, and no effort has been devoted to exploring such electrodes for PEC sensing.…”
mentioning
confidence: 99%